Rank effects in education: What do we know so far? - Judith Delaney; Paul J. Devereux (University College Dublin, UCD School of Economics, 2022)
In recent years there has been a plethora of empirical papers by economists concerning the effects of academic rank in school or college on subsequent outcomes of students. We review this recent literature, describing the difficult identification and measurement issues, the assumptions and methodologies used in the literature, and the main findings. Accounting for ability or achievement and across a range of countries, ages, and types of educational institutions, students that are more highly ranked in their class or their grade have been found to have better long-term outcomes. The effect sizes are generally large when compared to magnitudes found for other factors and interventions. Rank effects can provide useful insight into other educational phenomena such as the extent to which students benefit from high ability peers and the presence of a gender gap in STEM. However, the state of knowledge has probably not reached the point where the empirical findings from this literature have practical implications for policy intervention to improve outcomes of students.
Keywords: I21; J16; J24; 330; academic rank; education; human capital; social comparisons; peer effects; STEM